Maternal Pre-Pregnancy BMI and Gestational Weight Gain Are Associated with Preschool Children's Neuropsychological Outcomes in the APrON Cohort - Gillian England-Mason; Alida Anderson; Rhonda C. Bell; Fatheema B. Subhan; Catherine J. Field; Nicole Letourneau; Gerald F. Giesbrecht; Deborah Dewey; The APrON Study Team (MDPI AG, 2023)
This study examined the associations between maternal pre-pregnancy BMI and gestational weight gain (GWG) and children's neuropsychological outcomes at 3 to 5 years of age. A total of 379 women and their children from the Alberta Pregnancy Outcomes and Nutrition (APrON) study participated. Covariate-adjusted robust regressions examined associations between maternal pre-pregnancy BMI, GWG class, interaction terms, and child outcomes. Each unit increase in maternal BMI was linked to a 0.48-point decrement (95% CI: −0.75 to −0.21) in children's Full Scale IQ. Higher pre-pregnancy BMI was related to poorer performance on the other intelligence indexes (B = −0.35 to −0.47, 95% CIs: −0.75, −0.02) and lower performance on measures of language (B = −0.08 to −0.09, 95% CIs: −0.16, −0.02), motor skills (B = −0.08 to −0.11, 95% CIs: −0.18, −0.01), and executive function (B = −0.09 to −0.16, 95% CIs: −0.26, −0.01). GWG below the recommended range was associated with a 4.04-point decrement (95% CI: 7.89, −0.11) in Full Scale IQ, but better performance on a spatial working memory test (B = 0.27, 95% CI: 0.02, 0.52). GWG above the recommended range was associated with lower language (B = −0.79, 95% CI: −1.52, −0.06) and memory scores (B = −0.93, 95% CI: −1.64, −0.22). Interactions were found between pre-pregnancy BMI and GWG on measures of intelligence and executive function. Maternal pre-pregnancy BMI and GWG are related to children's performance in various neuropsychological domains and may interact to predict outcomes. Optimizing maternal health and weight prior to conception and during pregnancy may enhance children's neuropsychological outcomes.